Impacts of anthropogenic activities and calculation of the relative risk of violating surface water quality standards established by environmental legislation: a case study from the Piracicaba and Paraopeba river basins, Brazil - Soares, Ana Luiza Cunha; Pinto, Carolina Cristiane; Oliveira, Sílvia Corrêa (Environmental science and pollution research international, 2020)
The nonparametric test of Kruskal–Wallis and relative risk were used to evaluate surface water quality allowed to an identification of the most degraded water bodies in Piracicaba River and Paraopeba River basins, two important hydrographic basins in Brazil. Total manganese, dissolved iron, and fecal contamination indicator were considered the most relevant parameters for the characterization of water quality in the basins. The Peixe River, in Nova Era, and Pedras Creek, in Betim, were considered the most impacted water bodies in the Piracicaba River and Paraopeba River basins, respectively. The analysis of violations and the relative risk confirmed that both basins are subject to impacts resulting from economic activities. On comparing the relative risks, the Paraopeba River basin showed a higher risk of violation for 5-day biological oxygen demand (BOD 5 ), total manganese, total phosphorus, total suspended solids, and turbidity, while the Piracicaba River basin showed a higher risk of violation for fecal contamination indicator. The release of domestic sewage and industrial effluents, mining activities, and diffuse pollution from agriculture and pasture areas were responsible for the surface water quality deterioration in these basins. The results show the need for investment in basic sanitation, improved treatment efficiency for industrial effluents, adequate soil management, riparian vegetation preservation, and environmental education actions.